Clinical characteristics of children infected with enterovirus D68 in an outpatient clinic and the association with bronchial asthma. Issue 4 (3rd April 2018) - Itagaki, Tsutomu; Aoki, Yoko; Matoba, Yohei; Tanaka, Shizuka; Ikeda, Tatsuya; Mizuta, Katsumi; Matsuzaki, Yoko
Abstract: Background: All reports of increases in severe respiratory disease associated with human enterovirus D68 (EV-D68) are from hospital settings. However, there are few reports describing clinical characteristics in less severely affected populations. Methods: We conducted a retrospective observational study from January 2010 to December 2015 in Yamagata, Japan. Using regional passive surveillance, 5794 respiratory specimens were collected from children who initially presented to an outpatient clinic with acute respiratory symptoms. The collected samples were tested for EV-D68 by reverse transcription PCR. Results: EV-D68 was detected in 79 specimens mainly during the two epidemic periods in August–October 2010 and August–October 2015, when detection rates were 10.2% (31 of 304 specimens) and 16.3% (46 of 282 specimens), respectively. Among the 69 EV-D68-positive children, excluding those with viral coinfection, 39 (57%) had upper respiratory tract infections, 23 (33%) bronchiolitis or asthma attack, 5 (7%) bronchitis, 1 (1%) meningitis and 1 (1%) acute flaccid paralysis. In 23 children with wheezing, retraction was observed in 10 (43%), and six (26%) were diagnosed with asthma exacerbation. Six children required hospital admission, five (83%) because of asthma exacerbation. A history of asthma or wheezing was the most significant risk factor for the development of wheezing (odds ratio, 8.23; 95% CI, 2.65–25.50; p < .001). Conclusions: The low rate of hospitalization (9%, 6 of 69) indicates that most cases with EV-D68 infection were managed as outpatients. A history of asthma or wheezing was a potential risk factor for wheezing, resulting in hospitalization due to a severe asthma attack.